2020
DOI: 10.1097/gox.0000000000003071
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Major Upper Extremity Replantation: A Scoping Review

Abstract: Background: Traumatic upper limb amputations proximal to the carpus are devastating injuries. Existing literature on outcomes following replantation is limited. Our objective was to perform a scoping review of (1) functional outcomes; (2) return to work data; and (3) secondary surgeries required following proximal to carpus replantation. Methods: A literature search of MEDLINE, EMBASE, Cochrane, and CINAHL was performed according to PRISMA guidelines. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…This study reported a single case in which the follow-up period was not long and the most effective treatment was unknown. The outcome of this patient is not so good, considering the previous review that the average DASH score was 40.4 regardless of the replantation level, and 21% of elbow replantation was graded 4 (Poor) by Chen's functional criteria [4]. Changes in the patient's pain were not quantitatively identified because they changed frequently.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This study reported a single case in which the follow-up period was not long and the most effective treatment was unknown. The outcome of this patient is not so good, considering the previous review that the average DASH score was 40.4 regardless of the replantation level, and 21% of elbow replantation was graded 4 (Poor) by Chen's functional criteria [4]. Changes in the patient's pain were not quantitatively identified because they changed frequently.…”
Section: Discussionmentioning
confidence: 80%
“…However, only a few studies were reported on upper extremity replantation worldwide. A previous review revealed that the number of elbow replantation was the lowest, accounting for approximately 10% of study participants among the upper extremities, making this case relatively rare [4]. This study is different in that it specifically described the patient's progress in the short term while previous studies followed up in the long term over several years.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The lower replantation numbers, proximal to the elbow, might be amongst others attributed to the known less favourable functional replantation outcomes at these proximal levels. 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Bewertet wird das Ergebnis einer erfolgreichen Replantation primär durch den Unfallverletzten und sein engstes soziales Umfeld, während die objektive Beurteilung die funktionellen Ergebnisse nach Chen et al beinhaltet 2 , 15 , 16 , 17 , 18 .…”
Section: Prognose Und Ergebnisseunclassified